Episodes of dormancy and eruption of the Late Pleistocene Ciomadul volcanic complex (Eastern Carpathians, Romania) constrained by zircon geochronology - Molnár, Kata; Lukács, Réka; Dunkl, István; Schmitt, Axel Karl; Kiss, Balázs; Seghedi, Ioan; Szepesi, János; Harangi, Szabolcs (Journal of volcanology and geothermal research, 2019)
Ciomadul is the youngest volcanic system in the Carpathian-Pannonian Region recording eruptive activity from ca. 1Ma to 30ka. Based on combined zircon U-Th and (U-Th)/He geochronology, Ciomadul volcanism is divided into two main eruptive periods: Old Ciomadul (1Ma - 300ka; OCEP) and Young Ciomadul Eruptive Period (160-30ka; YCEP). OCEP activity comprises Eruptive Epochs 1-3, whereas new ages for eight lava domes and four pyroclastic units belonging to the YCEP lead to its further subdivision into two eruptive epochs: Eruptive Epochs 4 and 5. The extrusion of most of the lava domes occurred between 160 and 90ka (Eruptive Epoch 4) during three eruptive episodes at ca. 155ka, 135ka and 95ka (Eruptive Episodes 4/1, 4/2 and 4/3, respectively) along a NE-SW lineament, which is perpendicular to the regional NW-SE trend of the Călimani-Gurghiu-Harghita volcanic chain. Eruptive Epoch 5 occurred after a ca. 40 kyr of quiescence at ca. 55-30ka, and is mainly characterized by explosive eruptions with a minor lava dome building activity. All of the dated pyroclastic outcrops, together with the lava dome of Piscul Pietros, belong to the older Eruptive Episode 5/1, with an eruption age of 55-45ka. The eruption centers of Eruptive Epoch 5 are located at the junction of the conjugated NW-SE and NE-SW lineaments defined by the older eruptive centers. The whole-rock geochemistry of all studied samples is fairly homogeneous (SiO2=63-69wt%, K2O=3-4wt%). It also overlaps with the composition of the lava domes of the Old Ciomadul Eruptive Period, implying a monotonous geochemical characteristic for the past 1 Myr. The eruption rates for the Ciomadul volcanism were determined based on the erupted lava dome volume calculations, supplemented with the eruption ages. The activity peaked during the Eruptive Epoch 4 (160-90ka), having an eruption rate of 0.1km3/kyr. In comparison, these values are 0.05km3/kyr for the YCEP (160-30ka) and 0.01km3/kyr for the overall Ciomadul volcanism (1Ma-30ka). Based on the geochemical characteristics, the quiescence periods and the lifetime of the complex, as well as the relatively small amount of erupted material, this volcanic system can be placed in a subduction-related post-collisional geodynamic setting, which shows strong chemical similarities to continental arc volcanism. The commonly found long repose times between the active phases suggest that the nature of a volcano cannot be understood solely based on the elapsed time since the last eruption. Instead, comprehensive geochronology, coupled with the understanding of the magma storage behavior could be a base of hazard assessment for volcanic fields, where the last eruptions occurred several 10's of thousand years ago and therefore they are not considered as potentially active.